Discovery of Novel IDH1 Inhibitor Through Comparative Structure-Based Virtual Screening - Wang, Yuwei; Tang, Shuai; Lai, Huanling; Jin, Ruyi; Long, Xu; Li, Na; Tang, Yuping; Guo, Hui; Yao, Xiaojun; Leung, Elaine Lai-Han (Frontiers in Pharmacology, 2020)
IDH1 mutation occurs in 20–30% of gliomas and is a promising target for the cancer therapy. In present study, the performances of the different IDH1R132H were verified by using glide-docking-based virtual screening. Based on the two crystal structures (5TQH and 6B0Z) with the best capability to distinguish IDH1 inhibitors from decoys, a docking-based virtual screening was employed for identified novel IDH1R132H inhibitors. A total of 57 structurally diverse compounds were reserved and evaluated with experimental testing, and 10 of them exhibited substantial activity against the IDH1R132H (IC50 < 50 μM). Molecular docking technology showed that L806-0255, V015-1671 and AQ-714/41674992 could bind to the binding pocket composed of hydrophobic residues. These findings indicate that L806-0255, V015-1671 and AQ-714/41674992 have the potential for further optimization as a lead compound for the treatment of IDH1 mutated gliomas.